2016
DOI: 10.1038/nclimate3105
|View full text |Cite
|
Sign up to set email alerts
|

Satellite based estimates underestimate the effect of CO2 fertilization on net primary productivity

Abstract: Smith et al.1 (hereafter S15) compared global estimates of net primary production (NPP) derived from satellites and earth system models (ESMs). They concluded thatESMs over-estimate the effect of CO 2 fertilisation on NPP. An overestimation by ESMs is possible 2 , but here we draw attention to the fact that the satellite-derived NPP estimates used in S15 are likely to underestimate the CO 2 fertilisation effect because they do not account for the primary effect of CO 2 on the biochemistry of photosynthesis. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
71
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 19 publications
(12 reference statements)
2
71
0
Order By: Relevance
“…The effect of CO 2 concentration was found to be of some significance but not a key driver of RUE as found by De Kauwe et al (). This might be due to the fact that we analysed natural variability of CO 2 concentration (overall 380 ± 8 ppm) whereas De Kauwe et al () analysed long‐term FACE forest sites with CO 2 concentrations ranging from 370 to 550 ppm. A high CO 2 concentration may increase the effect of CO 2 on RUE.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The effect of CO 2 concentration was found to be of some significance but not a key driver of RUE as found by De Kauwe et al (). This might be due to the fact that we analysed natural variability of CO 2 concentration (overall 380 ± 8 ppm) whereas De Kauwe et al () analysed long‐term FACE forest sites with CO 2 concentrations ranging from 370 to 550 ppm. A high CO 2 concentration may increase the effect of CO 2 on RUE.…”
Section: Discussionsupporting
confidence: 53%
“…In a recent study, Fernández‐Martínez et al () tested the relationship between RUE and N deposition but no significant association was found. Finally, De Kauwe, Keenan, Medlyn, Prentice, and Terrer () have recently shown that CO 2 is a key factor controlling RUE variability. These authors found a large increase in RUE due to elevated CO 2 for two long‐term free air carbon enrichment (FACE) forest sites (Oak Ridge: 1998–2008 and Duke: 1996–2007).…”
Section: Introductionmentioning
confidence: 98%
“…With N constraint, the simulated global terrestrial GPP decreased by 1.4 Pg C yr −1 in 2015, dampening our expectation for the enhanced CO 2 fertilization. Our result may provide new explanation for the discrepancies between Smith et al () and De Kauwe et al () regarding the large divergence of LUE‐based and ESMs estimates of global terrestrial CO 2 fertilization. Therefore, the consideration of both LUE increase and reduced CO 2 fertilization under N limitation is necessary for accurate projections of future C‐climate feedbacks for different Representative Concentration Pathways.…”
Section: Discussionsupporting
confidence: 50%
“…We note, however, that the ratio of two out of six models including carbon-nutrient interactions in the ISIMIP ensemble is commensurate to other model inter-comparison projects: 3 out of 10 CMIP5 models (Exbrayat et al, 2014) or 2 out of 8 models in the new ISIMIP experiments presented by Chen et al (2017). There is also considerable debate on how good large-scale NPP observational products are de Kauwe et al, 2016), a problem that we address by performing the REA approach three times.…”
Section: Discussionmentioning
confidence: 99%